Vosviewer Application on Islamic Social Investment - Uula, Mimma Maripatul (Fara'id and Wealth Management, 2023)
This study aims to see the development of research on the topic of Islamic Social Investment and research plans that can be carried out based on journals published on the theme. This research uses a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme "Islamic Social Investment" which comes from the Scopus database with a total of 309 journal articles. Then, the data is processed and analyzed using the VosViewer application with the aim of knowing the bibliometric map of Islamic Social Investment research development in the world. The results of the study found that, based on bibliometric keyword mapping there are 7 clusters that can become research paths with topics related to Islamic Finance and Responsible Investment, Corporate Governance & Islamic Social Investment, Financial Cooperation & Islamic Social Investment, Waqf & Islamic Social Investment, Fintech & Islamic Social Investment, Economic Growth & Islamic Social Investment, and Covid-19 & Sustainable Islamic Social Investment. Furthermore, the most used words are country, Islamic bank, performance, investor, value, institution, international economics, risk, sukuk, and waqf.